1992
DOI: 10.1002/mc.2940050311
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of cathepsins L and B and decreased activity of their inhibitors in metastatic, ras‐transformed NIH 3T3 cells

Abstract: We previously found that the T24 Ha-ras oncogene induces metastatic ability in NIH 3T3 cells and that this change depends on expression of the ras oncogene. As part of our studies on mechanisms by which ras may induce metastasis, we investigated expression and activity of two cysteine proteinases, cathepsin L (major excreted protein) and cathepsin B, as well as cysteine proteinase inhibitor activity, in ras-transformed NIH 3T3 cells. In a series of cel lines that expressed differing amounts of ras, we found a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 43 publications
10
40
0
Order By: Relevance
“…Since high levels of protease activity are known to exist in the microenvironment of many tumours, particularly at the tumour -stroma interface, and increased protease production occurs in a variety of transformed cells (Rubin, 2003), tumours present an ideal environment for reovirus replication. Furthermore, cells transformed with oncogenic Ras have increased expression of proteases (Chambers et al, 1992), and we have shown that reovirus selectively infects cells with an activated Ras pathway Strong et al, 1998). Collectively, our data suggest that the proteolytic environment in tumours probably facilitates reovirus uncoating, and this could account for its enhanced oncolytic capability in vivo.…”
Section: Discussionmentioning
confidence: 62%
“…Since high levels of protease activity are known to exist in the microenvironment of many tumours, particularly at the tumour -stroma interface, and increased protease production occurs in a variety of transformed cells (Rubin, 2003), tumours present an ideal environment for reovirus replication. Furthermore, cells transformed with oncogenic Ras have increased expression of proteases (Chambers et al, 1992), and we have shown that reovirus selectively infects cells with an activated Ras pathway Strong et al, 1998). Collectively, our data suggest that the proteolytic environment in tumours probably facilitates reovirus uncoating, and this could account for its enhanced oncolytic capability in vivo.…”
Section: Discussionmentioning
confidence: 62%
“…The mechanism by which Ras activation increases reovirus growth has been suggested to involve inactivation of the interferoninduced eIF2␣ kinase PKR (64). Interestingly, it has been demonstrated that Ras activation can result in increased expression of various proteases, including cathepsin L (17,18,44). Since reovirus infection can be mediated by cathepsin L, higher levels of this protease could make Ras-activated cells more permissive to infection.…”
Section: Discussionmentioning
confidence: 99%
“…The level of cathepsin B expression is elevated in human breast and ovarian cancers (Woynarowska et al, 1989;Gabrijelcic et al, 1992;Lah et al, 1992), and in several metastatic cell lines, including ras-transformed NIH 3T3 cells and Lewis lung carcinoma cells, in which the level of expression has been correlated with the increased malignancy (Brodt et al, 1992;Chambers et al, 1992). In many malignant cell lines, the enzyme is localized to the plasma membrane and is clearly secreted in most instances (Sloane et al, 1986).…”
Section: Discussionmentioning
confidence: 99%